Fear of COVID-19, prolonged smartphone use, sleep disturbances, and depression in the time of COVID-19: A nation-wide survey - Li, Gangqin; Liu, Hao; Qiu, Changjian; Tang, Wanjie (Frontiers in Psychiatry, 2022)
Background: The COVID-19 pandemic can have a wide range of behavioral and psychological effects on the general pop-ulation. This study examined the interactions between fear of COVID-19, daily smartphone use, sleep disturbance, and de-pression in the general population at the early stage of COVID-19. Methods: An online national-wide survey was conducted from March 20 to April 10, 2020. Sociodemographic information, including age, gender, educational attainment, vocation, and duration of self-isolation, was collected; Fear of COVID-19 and other objective exposures, daily hours of smartphone use, night sleep duration, sleep disturbance, and depressive symptoms were measured with structured questions and PHQ-9. There were 1280 questionnaires in total, and 1250 valid questionnaires remained. Results: The prevalence of sleep disturbance and depression were found to be 13.1% and 10.7%, respectively. Feeling ex-tremely scared, longer smartphone use, difficulty initiating sleep and early morning awakening were significant risk factors for depression. Daily hours of smartphone use, difficulty in initiating sleep, and early morning awakening partially mediated the association between feeling extremely scared of the pandemic and depression. Conclusions: Psychological interventions in a major public health crisis should pay more attention to the subjective per-ception of the pandemic fear. At the same time, daily smartphone use and sleep disturbances could serve as targets for monitoring and intervention for depression during a pandemic.